INDIVIDUAL –DIFFERENTIATED APPROACH- IN THE MOTOR RECOVERY SYSTEM OF PRESCHOOL CHILDREN WITH INFANTILE CEREBRAL PALSY - Dorgan Victoria (Sport şi Societate)
In this study we refer to anindividual-differentiated approach in the motor rehabilitation system of preschoolers with Infantile Cerebral Palsy (ICP) which is one of the main conditions for effective application of the recovery system. This consists in the complex examination of motor disorders, their differentiation and the individualization of the recovery process. In this sense, we propose a rehabilitation system through the means of physical education of preschoolers with CP depending on the severity of the motor disorders. To select the sets of physical exercises intended for individual or group recovery programs, it is not enough to classify motor disorders according to the maximum or final manifestation level. There is a need to differentiate and analyze the causes that led to the reduction of the final motor result, for this examining the temporal, spatial and energetic parameters.